THE STRATEGY OF THE HEAD OF SUKAJADI TOURISM VILLAGE TO EMPOWER YOUTH ORGANIZATIONS TO INCREASE TOURIST VISITS THROUGH DIGITAL COMMUNICATION - Atika Suri; Herik Kurniawan; Guritno Himantoro (Yayasan Azam Kemajuan Rantau Anak Bengkalis, 2026)
The high number of Tourism Villages in Indonesia represents a potential opportunity to attract tourists, which is expected to boost the local economy. Digital communication skills are needed as part of promotional efforts because today almost all prospective tourists obtain information about tourism villages online. This means that tourism villages without an online presence risk losing opportunities from the tourism sector. Digital communication tools are mostly mastered by younger people. The youth organization at the village level is known as *Karang Taruna*. Through the members of *Karang Taruna*, digital communication is expected to be carried out to promote their village. This study examines the strategy of the Head of Sukajadi Tourism Village, Pandeglang, Banten, in empowering *Karang Taruna* to increase tourist visits through digital communication, using the perspectives of Communication Strategy and Digital Communication. The research employs a descriptive qualitative method, with data collected through observation, in-depth interviews, and documentation. The Head of Sukajadi Village has implemented persuasive, participatory, and horizontal communication styles. Unfortunately, this strategy has not been entirely successful in changing the collective behavior of residents because it has not matched of the aspect of tangible economic incentives for the community. The *Karang Taruna* organization, from which much was expected, has been abandoned by many members due to economic pressures. Young people prefer to work in the city, while those who remain face the phenomenon of sectoral ego and become trapped in individual interests, prioritizing the promotion of their own business units rather than building the village’s collective brand. As a result, the identity of Sukajadi Tourism Village in the digital space has become weak and fragmented.